Species composition and heterogeneity of blowflies assemblages (Diptera: Calliphoridae) in urban-rural gradients at regional scale in Argentinean Patagonia - Patitucci, Luciano D. (2011)
Fil: Patitucci, Luciano D. ANLIS Dr.C.G.Malbrán. Centro Nacional de Diagnóstico e Investigación en Endemo-Epidemias; Argentina.